Quiet Stance Postural Control in Women Who Have a History of Brain Injury from Intimate Partner Violence: A Preliminary Study - Bradi R. Lorenz; Shambhu P. Adhikari; Jonathan D. Smirl; Colin Wallace; Quinn Malone; Brian H. Dalton; Paul van Donkelaar (Neurotrauma Reports)
Intimate partner violence (IPV) frequently results in brain injury (IPV-BI) among survivors, with potential long-term effects for both physical and psychological health. This study aimed to examine the impact of chronic IPV-BI on postural control with (eyes open, [EO]) and without (eyes closed, [EC]) visual cues. We hypothesized that more exposure to a history of IPV-BI would be associated with greater postural control disruptions. During quiet stance, a force plate recorded forces and moments from which center of pressure (COP) variables were calculated to assess postural control. In addition, we sought to explore the relationship between psychological factors with assessments including indices of post-traumatic stress disorder (PTSD) (Clinician-Administered PTSD Scale), depression (Beck’s Depression Inventory), and anxiety (Beck’s Anxiety Inventory). Forty women survivors of IPV between the ages of 20 and 50 years participated, with the extent of exposure to IPV-BI measured using the Brain Injury Severity Assessment (BISA) tool on a scale of 0–8. Mediolateral (ML) COP displacement amplitude and variability, as well as anteroposterior (AP) COP velocity, was greater with EC than EO (p < 0.05). When participants were stratified into those with a low (0–2) and high (6–8) BISA score, participants in the high BISA (6–8) group exhibited greater COP area, ML COP amplitude and variability than those in the low BISA group (0–2; p < 0.05). Multiple linear regression analysis revealed that, independent of BISA score, PTSD symptoms contributed to changes in balance variables during the EO condition (p < 0.05). Taken together, our findings indicate the extent of exposure to a previous history of IPV-BI is linked to impairments in postural control as assessed by a variety of COP parameters. Given that standing balance is critical for function and mobility during activities of daily living, postural control assessments could serve as a valuable tool in diagnosing chronic IPV-BI. Thus, our study emphasizes the need for further research to better understand the physiological and psychological factors related to IPV-BI.